EXTENDED GLASGOW OUTCOME SCALE AND CORRELATION WITH BISPECTRAL INDEX - Senapathi, Tjokorda Gde Agung; Suarjaya, I Putu Pramana; Sutawan, Ida Bagus Krisna Jaya; Arparitna, Ketut Yudi (Bali Journal of Anesthesiology, 2017)
Traumatic brain injury (TBI) is a major public health issue, which results in significant mortality and long-term disability. The profound impact of TBI is not only felt by the individuals who suffer the injury but also their caregivers and society as a whole. Clinicians and researchers require reliable and valid measures of long-term outcome not only to truly quantify the burden of TBI and the scale of functional impairment in survivors but also to allow early appropriate allocation of rehabilitation supports. In addition, clinical trials which aim to improve outcomes in this devastating condition require high-quality measures to accurately assess the impact of the interventions being studied. In this article, we review the properties of an ideal measure of outcome in the TBI population. Then, we will describe the measurement tools include: the Glasgow Outcome Scale (GOS) and extended Glasgow Outcome Scale (GOSe) in correlation with bispectral index (BIS).